Cultural Democracy in Learning English at Madura Boarding School - hafidz, moh (Penerbit STKIP PGRI Bangkalan, 2019)
English is the language of daily life (Nurotun: 2015) trains communication skills and job needs. This research describes and analyzes about how cultural democracy in learning English is applied, maintaining local language (Madurese language) and the role of kiai in curriculum making? The benefits of this study as a theoretical reference and practice in learning English to maintain local language and culture. This research was conducted at Madura Islamic boarding school using descriptive qualitative approach with ethnographic research design, data collection techniques through observation, interviews and documentation. While the way to analyze it using Donald A's analysis technique (2010) is familiarizing and organizing, coding and reducing, and interpreting and representing. The results are always encouraging tutors and students to shape the environment of English and develop students' knowledge with vocabulary mastery through the “settoran” method. Conduct observations and teachings through “Fantsy Morning” and “Bazar Exhibition” and involve managers and alumni in making policies. Learning uses cooperative models by writing text in groups and reading text aloud. Speaking using English as a pesantren regulation. Maintaining pesantren culture, starting to dress and learning activities. Conducting curriculum development through deliberation to evaluate the entire set of activities and learning outcomes. Assessing vocabulary mastery, writing skill and speaking skill successively. Learning a cultural democracy-based language maintains the pesantren's value system and enhances new abilities and knowledge of English and supports Madura (enggi-bhunten). While the role of the kiai in making curriculum is that there are those who are involved directly and indirectly.